Pathogenesis and Varietal Screening for Panama Wilt Disease of Banana in Pakistan - Nasreen Sultana; Khalil Ahmed Khanzada; Jawed Akhtar; Syed Asim Rehan Kazmi (Journal of Basic & Applied Sciences, 2019)
Banana is the world largest fruit crop with an annual production of 114 million tonnes and Pakistan produces 154,800 tons annually. Panama wilt caused by Fusarium oxysporum f. sp. cubense (Foc) is the most widespread and destructive banana diseases worldwide. In Pakistan Panama disease was first recorded in 2012 in few banana fields of district Thatta and Hyderabad in the Sindh. The infection processes and mechanisms of pathogenesis of Foc in relation to symptoms expression and evaluation of Cavendish varieties for panama wilt of banana were studied. Pathogenesis was confirmed by establishing Koch’s postulates. The experiment was to evaluate occurrences of necrotic and wilting symptoms and the disease intensity on banana suckers of Cavendish cultivar, two months plantlets were artificially inoculated with 106 conidia/ml suspension of Foc. Five tested Cavendish varieties viz., w11, G9, Basari, Pisang and BT10 showed low to high average of score of wilting and necrotic symptoms. Based on the calculation of disease intensities, all Cavendish varieties tested were identified as susceptible to Foc infection.